Lactic Acid Bacteria as Potential Biocontrol Agents for Fusarium Head Blight Disease of Spring Barley - Byrne, Micheal B.; Thapa, Ganesh; Doohan, FIona M.; Burke, James I. (Frontiers in Microbiology, 2022)
Fusarium head blight (FHB) is a devastating disease encountered by spring grown barley. Traditionally, synthetic chemicals have been used to control this disease on small grain cereals. A move towards biolog-ical control agents as part of sustainable agriculture is pertinent due to the evolutionary mechanisms em-ployed by fungal diseases to circumvent current protection strategies. This study evaluated the effect of six lactic acid bacteria isolates on the development of FHB under in vitro and glasshouse conditions. The rel-ative expression of Fusarium marker genes and transcription factors under Fusarium infection was exam-ined. Dual-culture assays observed inhibition zones of up to 10% and 17% of total plate area for L. am-ylovorus FST 2.11 and L. brevis R2∆, respectively. Detached-leaf assays validated the antifungal activity and showed the potential of all test isolates to significantly inhibit sporulation of Fusarium culmorum and Fusarium graminearum strains. Spray inoculation of lactic acid bacteria to barley spikelets prior to Fusarium spore application significantly reduced disease severity for five candidates (P < 0.05) under glasshouse conditions. Mycotoxin analysis revealed the ability of L. amylovorus DSM20552 to significantly reduce deoxynivalenol content in spikelets (P < 0.05). A preliminary gene expression study showed the positive influence of lactic acid bacteria on the expression of important defence related marker genes and transcription factors upon FHB. These results indicate the potential of lactic acid bacteria to be included as part of an integrated pest management strategy for the management of FHB disease. This strategy will re-duce FHB severity and deoxynivalenol (DON) contamination of spring barley leading to high acceptance in grain market.